Comparison Of Curcumin Extract And Coconut Oil With Steroids Therapy In Reducing The Symptoms Of Oral Submucous Fibrosis (Journal of Pharmaceutical Negative Results, 2023)
Background: Limited mouth opening due to fibrosis of oral mucosa is a major symptom of oral submucous fibrosis which a chronic illness. The aim of the management of this chronic illness is to improve mouth opening and relieve unpleasant symptoms so that the quality of life of sufferer can be improved. Studies have validated the role of curcumin in management of the symptoms of the disease due to its antioxidant, anti-inflammatory, and anti-fibrotic potential. Additionally, coconut oil application also have been found in improving the symptoms hence, the study was aimed to compare the efficacy of mixture of curcumin extract and coconut oil with conventional therapy in management of OSF.Methodology: This experimental study was conducted at tertiary care hospital of Karachi from October 2022 to March 2023. Diagnosed cases (N=30) of oral submucous fibrosis were recruited from the dental OPD and they were divided in to two groups, n= 15 group 1, received the coconut oil with curcumin extract and n=15, group 2 received the corticosteroids (0.1% beclomethasone lotion). Patients were counseled regarding the application of therapeutic agents on the fibrous bands in the oral cavity buccal mucosa and physiotherapy exercises of mouth were recommended. They were instructed to apply the therapeutic agents 2 times a day and follow-up was performed on every month.Results: The mean difference in pain/ burning sensation and interincisal opening was observed significant (p=<0.05) before and after the intervention in both the groups. Coconut oil with curcumin extract reduced the pain / burning sensation and increased the interincisal opening effectively as that of steroids (0.1% beclomethasone lotion).Conclusion: Application of coconut oil with curcumin extract facilitates the sufferers in managing pain/burning sensation and mouth opening effectively as that of steroids.